Rational Design of Porous Structured Nickel Manganese Sulfides Hexagonal Sheets‐in‐Cage Structures as an Advanced Electrode Material for High‐Performance Electrochemical Capacitors. Issue 10 (10th February 2020) - Khalafallah, Diab; Wu, Zongxiao; Zhi, Mingjia; Hong, Zhanglian
Abstract: The design of hierarchical electrodes comprising multiple components with a high electrical conductivity and a large specific surface area has been recognized as a feasible strategy to remarkably boost pseudocapacitors. Herein, we delineate hexagonal sheets‐in‐cage shaped nickel–manganese sulfides (Ni‐Mn‐S) with nanosized open spaces for supercapacitor applications to realize faster redox reactions and a lower charge‐transfer resistance with a markedly enhanced specific capacitance. The hybrid was facilely prepared through a two‐step hydrothermal method. Benefiting from the synergistic effect between Ni and Mn active sites with the improvement of both ionic and electric conductivity, the resulting Ni‐Mn‐S hybrid displays a high specific capacitance of 1664 F g −1 at a current density of 1 A g −1 and a capacitance of 785 F g −1 is maintained at a current density of 50 A g −1, revealing an outstanding capacity and rate performance. The asymmetric supercapacitor device assembled with the Ni‐Mn‐S hexagonal sheets‐in‐cage as the positive electrode delivers a maximum energy density of 40.4 Wh kg −1 at a power density of 750 W kg −1 . Impressively, the cycling retention of the as‐fabricated device after 10 000 cycles at a current density of 10 A g −1 reaches 85.5 %. Thus, this hybrid with superior capacitive performance holds great potential as an effective charge‐storage material. Abstract : The six is in : A hexagonal sheets‐in‐cage shaped nickel–manganese sulfide (Ni‐Mn‐S) composite with a unique porous feature is employed as an advanced electrode material with a high specific capacitance and excellent rate capability. As a hybrid asymmetric capacitor electrode, the established device achieves high power and energy densities with an outstanding cycling stability for 10 000 consecutive cycles of repeated charge/discharge processes. This composite holds great potential as a multifunctional material for energy storage.